Correlation between antifungal consumption and distribution of Candida spp. in different departments of a Lebanese hospital - Lyn Awad; Hani Tamim; Ahmad Ibrahim; Dania Abdallah; Mohammad Salameh; Anas Mugharbil; Tamima Jisr; Nabila Droubi; Kamal Zahran; Rima Moghnieh (Journal of Infection in Developing Countries)
Introduction: Recently there has been a significant increase in the incidence of fungal infections attributed to Candida species worldwide, with a major shift toward non-albicans Candida (NAC). Herein, we described the distribution of Candida species among different departments in a Lebanese hospital and calculated the antifungal consumption in this facility. We, then, correlated the consumption of antifungals and the prevalence of Candida species.